The role of social exclusion in the formation of suicidal ideation among the elderly in rural pension institutions - Wang, Pingda; Gao, Peng; Yu, Zehui (Frontiers in Psychology, 2022)
Introduction Social exclusion as well as a sense of belonging and depression have been identified as risk factors for suicide among older adults in pension institutions. In particular, the elderly living in rural pension institutions is more likely to have poor mental health and a higher incidence of suicidal ideation. This study explored the mechanism of social exclusion on suicidal ideation among the elderly in rural pension institutions, and the moderating effect of interpersonal trust. Methods The social exclusion experience scale, sense of belonging, depression self-rating scale (CES-D), suicidal ideation scale (BSI-CV), and interpersonal trust scale (ITS) were used to investigate the elderly in rural pension institutions. A total of 1,387 samples (53.35% female) were collected, ranging in age from 65 to 95 years (M = 72.8, SD = 6.173). Results The results of the study found that: (1) social exclusion increases the suicidal ideation of the elderly in rural pension institutions, and the sense of belonging and depression play a significant chain-mediated role in the relationship between social exclusion and suicidal ideation in the elderly. (2) Interpersonal trust moderates the impact of social exclusion on the sense of belonging, depression, and suicidal ideation. Specifically, interpersonal trust can alleviate the promotion effect of social isolation on suicidal ideation and depression, and can also reduce the adverse effect of social exclusion on the sense of belonging. Discussion This study validates that social exclusion is a risk factor for suicidal ideation in the rural elderly and identifies interpersonal trust as a protective factor against social exclusion and its negative outcomes in the elderly. This study provides a scientific basis for improving the depression status of the elderly in rural China and formulating suicide prevention measures.